The extinguishment of lay midwifery in Portugal: A socio-historical analysis illustrated by 16th to 20th century literature - Santos, M. J. D. S (Recommitting to reproductive justice: Care ethical perspectives, 2025)
This article reflects on the social processes behind the disappearance of lay midwifery in Portugal, evoking the image of the community midwife in Portuguese literature from the 16th to the 20th century. With the development and standardization of maternity care, childbirth devolved into an institutional and bureaucratic event, erasing the diversity of birth practices and birth experiences, where women’s agency and the opportunities to control their birthing options are very limited. Using the lens of Ethics of Care, I analyze the extinct community midwives as promoters of reproductive justice, further discussing how the implementation of new models of institutionalized childbirth care stemming from medicalization led to less visible but wide-raging inequalities and reproductive injustice.